2001
DOI: 10.1128/iai.69.11.6670-6675.2001
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B27 Expression Does Not Modulate IntracellularChlamydia trachomatisInfection of Cell Lines

Abstract: Chlamydia trachomatis is an obligate intracellular pathogen. Infection of susceptible individuals with this bacterium can trigger the development of reactive arthritis, an acute inflammation that is associated with the expression of the class I major histocompatibility antigen, HLA-B27. Other facultative intracellular pathogens, such as Yersinia and Salmonella spp., are also known triggers of reactive arthritis. Previous studies report conflicting results concerning whether the presence of HLA-B27 modulates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…C. trachomatis serovar L2 was used throughout this study, and was purified from infected HeLa cells as previously described [12]. DC were infected with C. trachomatis (50:1 bacteria per cell) at day 7 of culture and used 24 h post infection, this being sufficient time to induce productive infection [13].…”
Section: Preparation Of Dendritic Cells and Infection With C Trachommentioning
confidence: 99%
“…C. trachomatis serovar L2 was used throughout this study, and was purified from infected HeLa cells as previously described [12]. DC were infected with C. trachomatis (50:1 bacteria per cell) at day 7 of culture and used 24 h post infection, this being sufficient time to induce productive infection [13].…”
Section: Preparation Of Dendritic Cells and Infection With C Trachommentioning
confidence: 99%
“…Following incubation for 48 h, cells were fixed with methanol and stained with anti-cLPS monoclonal antibody, and the presence of inclusion bodies was measured by fluorescent microscopy. Intracellular staining of PPEC followed by flow cytometric analysis was performed on cells 48 h after the infection following the protocol described by Young et al (49). Briefly, cells were harvested by incubation with trypsin-EDTA (Sigma) for the intracellular staining; cells were then incubated with the antiChlamydia LPS monoclonal antibody or an appropriate isotype control in fluorescence-activated cell sorter wash buffer (5 mM EDTA, 0.1% sodium azide, and 1% bovine serum albumin in PBS) supplemented with 0.1% saponin for 30 min at 4°C.…”
mentioning
confidence: 99%
“…In contrast, some investigators have found that HLA-B27 expression alters neither the rates of infection nor the rate of replication of C. trachomatis in cell lines (24). Using synoviocytes harvested from HLA-B27-positive patients, it was observed that HLA-B27 had no direct role in either the internalization of S. typhimurium or in the kinetics of intracellular killing (25).…”
Section: Human Leukocyte Antigen-b27 and Direct Host-pathogen Interacmentioning
confidence: 91%